Characterization of Some Copper(II), Nickel(II) and Cobalt(II) Coordination Compounds with Schiff Bases Derived from 1,2-Dipenyl-1-Hydroxyiminoethan-2-One and Aromatic Amines - Rai, H.C.; Kumar, Ramesh; Kumar, Sunil (Asian Journal of Chemistry, 2010)
A number of coordination compounds of the types [M(L1–7)2], [M(HL1–7)2Cl2] [M =Co(II), Ni(II) or Cu(II)] and [CuL1–7 Cl], where HL1–7 = Schiff bases derived by condensing 1,2-diphenyl-1-hydroxyiminoethan-2-one with aniline (HL1), 2-methylaniline (HL2), 3-methylaniline (HL3), 4-methylaniline (HL4), 2-nitroaniline (HL5), 3-nitroaniline (HL6) or 4-nitroaniline (HL7) have been synthesised and characterised on the basis of elemental analyses, magnetic susceptibility, infrared and electronic spectral data.